2002
DOI: 10.1074/jbc.m200108200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric States of the Detergent-solubilized Human Serum Paraoxonase (PON1)

Abstract: Human plasma paraoxonase (HuPON1) is a high density lipoprotein (HDL)-bound enzyme exhibiting antiatherogenic properties. The molecular basis for the binding specificity of HuPON1 to HDL has not been established. Isolation of HuPON1 from HDL requires the use of detergents. We have determined the activity, dispersity, and oligomeric states of HuPON1 in solutions containing mild detergents using nondenaturing electrophoresis, size exclusion chromatography, and crosslinking. HuPON1 was active whatever its oligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 52 publications
3
48
0
1
Order By: Relevance
“…Other key properties of PON1 seem to be retained in the newly evolved variants. Like HuPON1 (17), rePON1s appear to be in monomer-dimer equilibrium in the presence of 0.6 mM C 12 -maltoside, as analyzed by gel filtration (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other key properties of PON1 seem to be retained in the newly evolved variants. Like HuPON1 (17), rePON1s appear to be in monomer-dimer equilibrium in the presence of 0.6 mM C 12 -maltoside, as analyzed by gel filtration (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The two mutated regions in the newly evolved PON1s may be involved in correct folding of PON1 and in its oligomeric packing. It has been suggested that exposed hydrophobic surfaces of PON1 are involved in its oligomerization and aggregation (17). These putative hydrophobic surfaces may also lead to aggregation of wild-type PON1s when expressed in E. coli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A2 and B2) reflects the good quality of the fit versus the experimental values. It should be mentioned that the analysis of analytical centrifugation data recorded in the presence of detergent is complicated by the fact that the amount of detergent bound to the studied protein is generally unknown, and thus several hypotheses must be considered (30,80). In the presence of 0.1% DM, C HCV 169* migrates as a homogeneous species with a sedimentation coefficient of 3.1 Ϯ 0.1 S (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that PON1 Leu-9, Tyr-185, and Tyr-293 participate in PON1-HDL interactions, and the nature of the site-specific mutations impact the affinity of the PON1 form to bind to HDL. PON1 binding to HDL is known to stabilize PON1 catalytic activity at 37°C, with both protein (apoA-I) and lipid phase of HDL contributing to the overall docking and stabilization of PON1 on the HDL particle (31,74,75). We therefore next analyzed the importance of PON1 Leu-9, Tyr-185, and Tyr-293 in PON1 stabilization with HDL particles.…”
Section: Pon1 Residues Leu-9 Tyr-185 and Tyr-293 Are Functionally Imentioning
confidence: 99%